2013 IEEE 1st International Conference on Condition Assessment Techniques in Electrical Systems (CATCON) 2013
DOI: 10.1109/catcon.2013.6737522
|View full text |Cite
|
Sign up to set email alerts
|

Life estimation of transformer insulation under repeated impulses

Abstract: Oil Impregnated Paper (OIP) is commonly used dielectric material in transformer windings. The most of the transformer winding failures are due to breakdown of dielectric material. The breakdown mechanism of composite dielectric undergoes gradual degradation in nature. OIP is subjected to rapid degradation when it is subjected to overvoltages. The severity of the degradation depends on steepness of the waveshape. It is necessary to analyze the characteristics of OIP for varying wavefronts (t f ) ranging from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This degrades the insulation system [2]. The insulation degrades more on repeated exposure to impulses [3,4]. The severity of insulation degradation depends on steepness of the wave, instant of chopping, time to collapse, frequency of oscillations, overshoot near the peak, etc.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This degrades the insulation system [2]. The insulation degrades more on repeated exposure to impulses [3,4]. The severity of insulation degradation depends on steepness of the wave, instant of chopping, time to collapse, frequency of oscillations, overshoot near the peak, etc.…”
Section: Introductionmentioning
confidence: 98%
“…The severity of insulation degradation depends on steepness of the wave, instant of chopping, time to collapse, frequency of oscillations, overshoot near the peak, etc. [1,3,5]. Aschlimann [6] and Sirotinski [7] showed that voltage stresses due to chopped waveforms were higher than those due to full wave of the same steepness.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, in 1996, it was pointed out that oil-paper insulation used in power transformers broke down prematurely when subjected to repetitive impulse voltages [6]. Later, in the 2010s, and following an appeal by Okabe, an increasing number of researchers began to study the accumulative failure phenomenon in oil-paper insulation subjected to repetitive impulse voltages and many useful results were obtained [7][8][9]. The present paper reviews important achievements made in recent decades with regards to the accumulative failure of winding insulation subjected to repetitive impulse voltages and discusses future challenges in this research area.…”
Section: Introductionmentioning
confidence: 99%